La médiation des petits États : rétrospective et perspective (Note) - Allouche, Boussetta (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
Propped by Norway's diplomatic breakthrough in getting Israel and the PLO to forego their protracted state of war and negotiate their way toward a peaceful coexistence, this study focuses on small state mediation. It is an intellectual endeavor to shed light on a small state intervening as a third party mediator in some conflict-ridden international disputes. Because of the normative and legalistic approach that has dominated the study of international relations for quite some time, it is not surprising that the process of mediation can be difficult to grasp or, at least, subject to misunderstanding. Highlighting the small state mediation paradigm, the essay sets out Us background and offers an interpretative analysis of Us value. It addresses a number of questions pertaining to this avenue for international conflict management. For instance, where does international mediation fit within the larger spectrum of international peace mechanisms ? What are the distinguishing features of a small state's style of intervention, and how does a small state mediation differ from other mediatory schemes such as those intiated by other actors ? Most importantly, where does a small state's wherewithal to bring about a peaceful settlement of an international dispute stem from ? These and other questions are carefully probed in an attempt to grasp the dynamic of small state mediation.